2017
DOI: 10.1111/tbed.12752
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the epidemic characteristics and evolutionary history of the novel porcine circovirus type 3 in southern China

Abstract: Porcine circovirus type 3 (PCV3) is a newly identified circovirus from swine in the USA, China and Poland. This novel circovirus has been associated with porcine dermatitis and nephropathy syndrome (PDNS), reproductive failure and multisystemic inflammation; moreover, PCV3 poses a potential threat to the swine industry. In this retrospective study, a phylogenetic analysis was conducted to address the epidemiology and evolutionary dynamics of this novel circovirus. The total positive sample rate of PCV3 was 26.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
146
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(161 citation statements)
references
References 33 publications
12
146
3
Order By: Relevance
“…Among the amplicons from the four strains, there were only point mutations, but no nucleotide deletions or insertions. Based on the sequence analysis and comparison with the US MN2016 strain (KX898030), eleven aa changes were observed; PCV3 strains from this study and all reference strains had D56N and K100T mutations, and the SP strain had nine unique changes (P59A, W72G, E73G, S77R, K100T, R132P, I150N, A152G, T179P and K204Q), whereas three Chinese strains (CN/Fujian‐5/2016, CN/Fujian‐12/2016 and CN/Henan‐13/2016), two South Korean strains (KU‐1602 and KU‐1604), the Brazilian BR/RS/6 strain, and 29160 strain from the United States contained S77T and I150L mutations, which were also found in a previous study (Fu et al., ). We concluded that PCV3 strains from central China exhibited rapid mutation, possibly by means of international trading from other countries.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Among the amplicons from the four strains, there were only point mutations, but no nucleotide deletions or insertions. Based on the sequence analysis and comparison with the US MN2016 strain (KX898030), eleven aa changes were observed; PCV3 strains from this study and all reference strains had D56N and K100T mutations, and the SP strain had nine unique changes (P59A, W72G, E73G, S77R, K100T, R132P, I150N, A152G, T179P and K204Q), whereas three Chinese strains (CN/Fujian‐5/2016, CN/Fujian‐12/2016 and CN/Henan‐13/2016), two South Korean strains (KU‐1602 and KU‐1604), the Brazilian BR/RS/6 strain, and 29160 strain from the United States contained S77T and I150L mutations, which were also found in a previous study (Fu et al., ). We concluded that PCV3 strains from central China exhibited rapid mutation, possibly by means of international trading from other countries.…”
Section: Resultsmentioning
confidence: 85%
“…() and Fu et al. (), who found that PCV3 could be detected as early as 2014 in Hebei Province and in February 2015 in Guangxi, Guangdong, Jiangxi, Fujian and Hunan provinces, respectively. Most recently, a retrospective study of PCV3 infection in China found that 6.5% of the porcine samples collected from eight provinces and one autonomous region (Guangxi, Guangdong, Hainan, Hunan, Yunnan, Sichuan, Qinghai, Zhejiang and Jilin) were PCV3 positive, with the earliest cases occurring in 1996.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Phylogeny‐based studies searching for the origin of PCV3 show the oldest trace of origin around 1966 from bats circovirus (Fu et al . ). In pigs, the presence of PCV3 has been verified since 1996 in Spain, where it was also shown that there have not been many changes since then (Klaumann et al .…”
Section: Introductionmentioning
confidence: 97%